Knowledge And Attitudes Towards First Aid Among Undergraduate Students At Rafflesia College, Unimas - Le, Shuqi Andra Ju (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Background: Accident and injuries may happen anytime and anywhere and this incident may take place outside of the hospital setting. Thus, first aid is essential to help those in need. First aid is not only minimise the wound deterioration but also reduce the mortality rate. Objectives: The study aimed to assess the first aid knowledge, attitude towards first aid, and its association with socio-demographic characteristics. Methodology: A quantitative cross-sectional study was conducted among 343 undergraduate students at Rafflesia College, UNIMAS, by using a convenience sampling method. Data collection were done by using a self-administered questionnaire adopted from Jamaludin et al. (2018) via google form. The knowledge of first aid were assessed with 10 questions whilst attitude towards first aid were assessed with 5 questions. Results: Six responses were exempted from the study due to missing data, thus bringing up a final sample of 337 respondents. A total of 51.6% respondents had moderate first aid knowledge and 83.4% of the respondents showed good attitude towards first aid. Faculty and first aid training was significantly associated with knowledge of first aid. However, there were no significant association between all of the socio-demographic characteristics and the attitude towards first aid. Conclusions: The findings showed that most of the respondents had moderate knowledge and attitude towards first aid. However, there is a need to introduce the first aid course in every faculty in the university to enhance the first aid knowledge not only among health sciences students but also non-health sciences students.